Efects of scan speed and laser power at the geometic quality of materials manufactured using Selective Laser Fusion SLF (LACCEI, 2024)
Additive manufacturing techniques are an extensive and broadly used technology that allows to create metal pieces with complicated geometric forms in less time and reduces cost compared to classic manufacturing techniques such as machining. Selective Laser Melting (SLM) and Selective Laser Fusion (SLF) are some of the different techniques of Additive Manufacturing that use high-energy Laser to build metal pieces from a 3D model. Although these techniques are cheaper and faster than other additive manufacturing techniques, they have some surface and geometrical problems such as high roughness, pores, and nominal radios different from those used in the CAD model. Some authors have described that by modifying some manufacturing parameters such as scan speed, laser power, or scan strategy, some of those problems can be fixed or reduced. This investigation evaluated the effect of scan speed and power of Laser over the geometrical quality of pieces made using Selective Laser Fusion technique (SLF). This investigation found that these two parameters didn´t have any statistical effect on the quality of geometrical radios made using SLF. Other parameters such as Laser scan strategy or post-process might be used to improve geometrical quality in pieces made using that technique.